The Encryption Code: The Symbolic Language of Alchemy Engraving Books - Ferrer Ventosa, Roger (Actual Problems of Theory and History of Art, 2018)
The aim of the article is to show the artistic value of the alchemical engraving books of the 16th–18th centuries. These books provide art historians with a sophisticated visual symbolic language. The common understanding about alchemy is made of biases and wrong conceptions, even in scientific and historical milieu. In fact, these preconceptions began precisely in this milieu, especially from Enlightenment intellectuals, even though some of the most remarkable scientists in those years studied both chemistry and alchemy, chymistry, such as George Starkey, Robert Boyle or even Isaac Newton. Symbolical books of this kind are especially interesting for their use of a codified visual language, a way of sharing knowledge by visual skills. Those artists communicated ideas that would not be understood by someone who was not an expert in the subject. Moreover, with this ciphered symbolic language, they provided themselves with protection in times of persecutions. Moreover, alchemy’s cultural horizon is one of the few cases of non-dualism in the Western way of thinking. That is one of the main ideas showed in these engraving books. In alchemy we find several iconographic motifs representing non-dual theories in a visual way. One of them is the representation of a human being with two sexes, an androgyne or a hermaphrodite. A second iconographic motif about non-dualism in that background is the Sacred Wedding: a couple embraced and making love, named hieros gamos by ancient Greeks. The alchemical framework had a strong influence on some artists of later periods such as William Blake, Max Ernst, or Leonora Carrington and deserves that art historians put more attention to its symbolic language.